Information security : 22nd international conference, ISC 2019, New York City, NY, USA, September 16-18, 2019 : proceedings /: 22nd international conference, ISC 2019, New York City, NY, USA, September 16-18, 2019 : proceedings. ([2019]) - Unknown
No abstract available